The Pictorial Health Warnings Impact on Smoking Cessation Intention: A Literature Review Based On TPB - Sandra Reinny Parengkuan; Nur Rohmah; Annisa Nurrachmawati (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Cigarette consumption in Indonesia remains high, underscoring the need for effective tobacco control strategies such as Pictorial Health Warnings (PHWs). This study aims to analyze the influence of PHWs on the components of the Theory of Planned Behavior (TPB)—attitude, subjective norm, and perceived behavioral control—and their subsequent effect on the intention to quit smoking. Objective : This study aims to analyze the influence of PHWs on the components of the Theory of Planned Behavior (TPB)—attitude, subjective norm, and perceived behavioral control—and their subsequent effect on the intention to quit smoking Research Methods/ Implementation Methods : A systematic literature review was conducted using indexed scientific databases, including Scopus, DOAJ, and PubMed, for the period of 2020–2024. The review included three primary studies that met the inclusion criteria and focused on smoking cessation behavior, the TPB framework, and pictorial media as an intervention. This study adopts the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method in the process of identifying and selecting literature studies. Results : The findings consistently demonstrate that graphic visualizations of smoking-related hazards positively influence smokers' attitudes, enhance social awareness (subjective norm), and strengthen perceived behavioral control over quitting. Conclusion/Lesson Learned : In conclusion, PHWs effectively target the key determinants of behavioral intention outlined in the TPB. An emotionally powerful visual approach significantly boosts smokers' awareness and motivation to quit, affirming the utility of PHWs as a critical public health intervention.